Optimal Brain 99mTc–Ethyl Cysteinate Dimer SPECT Imaging and Analysis to Detect Misery Perfusion on 15O PET Imaging in Patients With Chronic Occlusive Disease of Unilateral Major Cerebral Artery - Matsumoto, Yoshiyasu (Clin Nucl Med, 2017)
PURPOSE: Misery perfusion is defined as marginally sufficient cerebral blood supply relative to cerebral metabolic demand. The aim of the present study was to determine the optimal brain (99m)Tc–ethyl cysteinate dimer (ECD) SPECT imaging and analysis to detect misery perfusion on (15)O PET imaging in patients with chronic occlusive disease of unilateral internal carotid or middle cerebral artery (MCA). METHODS: For 97 patients, cerebral blood flow, cerebral metabolic rate of oxygen, and oxygen extraction fraction were measured using (15)O PET; (99m)Tc-ECD SPECT was performed using dynamic scanning with a scan duration of 10 minutes each for 50 minutes after tracer administration. A region of interest was placed in the bilateral MCA territories and in the bilateral cerebellar hemispheres in all standardized images using a 3-dimensional stereotaxic region-of-interest template and affected-to-contralateral asymmetry ratio in the MCA territory (AR(MCA)) and contralateral-to-affected asymmetry ratio in the cerebellar hemisphere (AR(cbl)) were calculated. RESULTS: The AR(MCA) or AR(cbl) on (99m)Tc-ECD SPECT with a scan time of 20 to 30 minutes after tracer administration (AR(MCA20–30) or AR(cbl20–30)) was correlated with AR(MCA) on PET cerebral blood flow (r = 0.654) or AR(MCA) on PET cerebral metabolic rate of oxygen (r = 0.576), respectively, more strongly than with other scan times. The area under the receiver operating characteristic curve for detecting abnormally elevated AR(MCA) on PET oxygen extraction fraction was significantly greater for AR(cbl20–30)/AR(MCA20–30) (0.947) than for AR(MCA20–30) alone (0.780) (difference between areas, 0.167; P = 0.0001) on (99m)Tc-ECD SPECT. CONCLUSIONS: Combination of asymmetries in the cerebellar and cerebral hemispheres on (99m)Tc-ECD SPECT in a scan time of 20 to 30 minutes after tracer administration optimally detects misery perfusion in unilateral internal carotid artery or MCA occlusive disease.